Effect of Hypecoum erectum Extract on Morphofunctional State of the Liver in Rats with Tetracycline-Associated Hepatitis - A. A. Toropova; S. M. Nokolaev; Ya. G. Razuvaeva; A. V. Fedorov; Z. G. Sambueva; I. P. Ubeeva (Антибиотики и Химиотерапия, 2020)
The effect of Hypecoum erectum L. extract on the morphofunctional condition of the liver in rats with experimental tetracycline-associated hepatitis was studied. The experiment included 40 albino rats Wistar. The animals treated with tetracycline hydrochloride (1.0 g/kg body weight) were exposed to the extract in a dose of 50 mg/kg for 5 days. On the 7th day of the experiment the following indices were determined: malonic dialdehyde concentration, catalase activity, the levels of ATP, pyruvate and lactate in the liver homogenate, as well as the blood levels of reduced glutathione. The liver pathomorphological investigation was applied. The H.erectum extract was shown to inhibit lipid peroxidation, to increase the activity of the host endogenous antioxidant system, to normalize the hepatocyte energy provision and to limit the liver degeneration.